Agronomic Performance and Light Interception in a Multi Canopy Rice Cultivation System - Husna; Junaedi, Ahmad; Purnamawati, Heni (Department of Agronomy and Horticulture, IPB University, 2025)
Vertical space optimization through a multi-canopy system can potentially increase rice production. This research aims to evaluate the agronomic performance, light interception, and production of rice plants cultivated with a multi-canopy system. This research was conducted at the Sawah Baru Experimental Farm, IPB University. Rice varieties used two common height plants (“Inpari 30” and “Inpari 32”) and the taller plants (“IPB 9G”). This research consisting of nine treatment combinations of cultivation system: mono-variety (“Inpari 30”, “Inpari 32”, and “IPB 9G”), combination of two varieties in one hill multi-canopy (“Inpari 30”-“IPB 9G” and “Inpari 32”-“IPB 9G”), inter-variety one-insertion multi-canopy (“Inpari 30”-“IPB 9G” and “Inpari 32”-“IPB 9G”), and inter-variety two-insertion multi-canopy (“Inpari 30”-“IPB 9G” and “Inpari 32”-“IPB 9G”). The results showed morphological and physiological performance as good in a multi-canopy system (inter-variety one insertion) on the variables of the plant height, number of panicles per clump, panicle length, number of grains per hill, weight of grains per hill, photosynthetic rate and land equivalent ratio (LER). The percentage of light interception in the multi-canopy system decreased by 19.13-61.54%. The inter-variety one-insertion multi-canopy with the “Inpari 30”-“IPB 9G” combination increases yield potential by 10.18%, and the “Inpari 32”-“IPB 9G” combination increases by 13.81% compared to the mono-variety. The combination of the “Inpari 30”- “IPB 9G” and “Inpari 32”-“IPB 9G” variety in an inter-variety one-insertion multi-canopy system produces an LER value of 1.75 and 1.64; this shows that the inter-variety one insertion multi-canopy system is promising to increase rice production.